Affective Presence: The Metonymical Catalogue. (6th September 2016) - Krmpotich, Cara; Somerville, Alexander
Abstract: Drawing on exploratory research of online ethnographic records for particular types of Aboriginal bags in North America, we confront the absence of affective knowledge in museum catalogues and documentation. Although curatorial, ethnographic, and Aboriginal understandings of these items teem with affect, we find affect to be almost wholly lacking from available online records. We ask what the effects of this absence are for descendent Aboriginal communities, for museum publics, and for affect theory. We also look at an example where affect has a presence in online records, the Glenbow Museum, and consider the ways this creates opportunities for comparative and historic affective study.